COMPREHENSIVE ASSESSMENT OF BIOCHEMICAL MARKERS IN THE BLOOD IN PREGNANT WOMEN SUFFERING FROM HYPERTENSIVE DISORDERS - Людмила Васильевна Боровкова; Светлана Олеговна Колобова; Лариса Дмитриевна Андосова; Ксения Андреевна Шахова; Юлия Рудольфовна Тихомирова (The Publishing House Medicine and Enlightenment, 2022)
Aim - complex assessment of the content of biochemical markers endothelin-1 and sVCAM-1 in the 1-st trimester in pregnant women suffering from chronic arterial hypertension, depending on the development of large obstetric syndromes. Materials and methods. 84 pregnant woman aged 18-45 years were examined at 10-13 weeks of pregnancy. The main group consisted of 54 women suffering from arterial hypertension (stage I), the control group consisted of 30 healthy women. The levels of biochemical markers were determined in blood serum samples by solid-phase enzyme immunoassay. Results. According to the results of the study, it was revealed that women with hypertension in the 1-st trimester had statistically significantly higher levels of endothelin-1 and sVCAM-1 compared to healthy woman. Besides, in chronic arterial hypertension, pregnancy is significantly more often complicated by preeclampsia, fetal development delay and placental insufficiency compared with pregnant women without hypertensive disorders. It has been established that chronic arterial hypertension occurs against the background of an inflammatory process and a violation of the functional state of the vascular endothelium in the 1-st trimester in pregnant woman. Conclusion. Vascular adhesion molecule can act as a marker of chronic AH in pregnant women in the early stages of gestation. To assess the prognostic role of endothelin-1 in the development of large obstetric syndromes, further study of the significance of this peptide in a larger sample of patients, as well as in combination with other biochemical and biophysical markers, is required.